Ex post inequality of opportunity comparisons - Marc Fleurbaey; Vitorocco Peragine; Xavier Ramos Morilla (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
In this paper we propose different criteria to rank income distributions according to equality of opportunity. Different from existing ones, our criteria explicitly recognize the interplay between circumstances and effort. We characterize them axiomatically and we compare them with existing criteria; then we propose some scalar measures. We show that our ex post criteria are mostly obtained from "seemingly" ex ante properties. In the second part of the paper we apply our new criteria to measuring inequality of opportunity in Germany. We illustrate our ex-post inequality of opportunity approach based on classes by means of the German Socio-Economic Panel (SOEP) for the first decade of the 2000s.
Keywords: D3; D63; D71; 330; equality of opportunity; ex post/ex ante; compensation; reward; SOEP; Germany